The Challenges of Managing Destinations: Understanding Sustainability and Change through Destination Modelling - Jones, Tod; Wood, David (CAUTHE, 2009)
There is an increasing recognition that tourism research should shed light on the complexities and linkages within tourism systems, perhaps best summarised by Farrell and Twining-Ward's designation of tourism as 'a complex adaptive system' (2005). Such an understanding of tourism is closely linked to the concept of sustainable tourism, which recognises the importance of social, environmental and economic systems to collective quality of life and ultimately the survival of the planet (World Commission on Environment and Development, 1987). This is captured in Butler's often-used definition of sustainable tourism: Tourism which is developed and maintained in an area in such a manner and at such a scale that it remains viable over an indefinite period and does not degrade or alter the environment (human and physical) in which it exists to such a degree that it prohibits the successful development and wellbeing of other activities and processes (1993, p.29). While tourisms complexity and its diverse dimensions are well recognised, the processes for integrating this understanding into a research project are not well covered in the tourism research literature. This paper analyses the preliminary stages of a research project that examines and integrates social, environmental and economic systems in order to assist tourism planning at the destination level.